Sensitivity of A-549 human lung cancer cells to nanoporous zinc oxide conjugated with Photofrin - Muhammad, Fakhar-E-Alam; Syed Muhammad Usman, Ali; Zafar Hussain, Ibupoto; Kimleang, Khun; Muhammad, Atif; Mohammad, Kashif; Loong, Foo Kai; Uda, Hashim, Prof. Dr.; Willander, Magnus (Springer-Verlag London Ltd., 2012)
Link to publisher's homepage at http://www.springerlink.com/